Usability investigation of an educational mobile application for individuals with intellectual disabilities - Yeni, Sabiha; Cagiltay, Kursat; Karasu, Necdet (SPRINGER HEIDELBERG, 2020)
This research examined the usability of an interactive mobile application (tablet application) designed to teach daily living skills to individuals with intellectual disabilities (ID). Effectiveness, efficiency, and satisfaction aspects were investigated. The persistence of a newly learned skill, operating a vacuum cleaner, was assessed following training sessions. The study also examined how well participants generalized the skill to a different tool and setting after learning via the interactive tablet application. In addition, to determine the social validity of the study, five special education teachers' views (satisfaction levels) about the tablet application were examined. To determine the efficiency of the tablet application, differences in time of intervention sessions between the pilot study and the main study were investigated. A single-case research methodology was employed with a multiple baseline design. Furthermore, to identify the usability issues of educational tablet applications, heuristic evaluation and user test methods were used together. One male and four females with a diagnosis of intellectual disability took part in the study. All participants improved their ability to use the vacuum cleaner and performed the skill correctly following the intervention sessions. Performance during generalization and maintenance sessions also met defined success criteria. Efficiency data show that changes in the tablet application decrease the significant amount of time spent for intervention. It is an important result for individuals with ID who might not be able to focus attention over a longer period of time. The results of this study show that using the interactive tablet applications in the education of individuals with ID is an effective method for improving their daily living skills.
Keywords: Intellectual disabilities; Tablet application (mobile application); Daily living skills; Tablets; Mobile devices; Usability test; Heuristic evaluation; DEVELOPMENTAL-DISABILITIES; ASSISTIVE TECHNOLOGY; SOCIAL VALIDITY; STUDENTS; TEACHERS; CHILDREN; DEVICES; PEOPLE; IPOD; Computer Science; Engineering